The Traditional System of Qur’anic Education in Northern Nigeria (Tsangaya): Recipe For A Feasible and Sustainable Reform - Yahya, Ahmad; Muhammad, Aliyu Yunus; Ahmad, Mustapha; Fagge, Shehu Dahiru (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
Succumbing to absolute neglect, the Tsangaya system faces many avoidable problems. Most of the attempts made by some administrations to address these problems appeared to have been narrowed down to either abolishing the system or blending it with alien elements. The beautiful aspects of the system appeared to have been ignored. This paper, generating data from interviews and document analyses, attempts to bring out some of the ignored features of the Tsangaya system, the problems it faces and suggestions for a sustainable reform. The aim is to bring into light some aspects of the system which risks being lost amidst the blind attacks against Tsangaya and the way for a feasible and sustainable reform. The reason for selecting this topic is the present attempts being made to reform the Tsangaya system in Nigeria. The paper reveals that aspects such as student/teacher relationship, class management and control, assessment of student's academic performance, etc. are beautiful features of the system which the conventional education system could borrow and integrate. A holistic approach, including recognising the noble status of the system as the custodian of the Qur’an, its teachers and students, is suggested in order to realise a sustainable and feasible reform.